Sensitization Profiles of Timothy Grass Pollen in Northern China - Xu Y (Dove Medical Press, 2021)
Yingyang Xu,1– 3 Kai Guan,1– 3 Li Sha,4 Jinghong Zhang,5 Yongliang Niu,6 Jia Yin,1– 3 Lianglu Wang1– 3 1Department of Allergy, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100730, People’s Republic of China; 2Beijing Key Laboratory of Precision Medicine for Diagnosis and Treatment on Allergic Diseases, Beijing, 100730, People’s Republic of China; 3National Clinical Research Center for Dermatologic and Immunologic Diseases, Beijing, 100730, People’s Republic of China; 4Department of Allergy, Capital Institute of Pediatrics, Beijing, 100020, People’s Republic of China; 5Department of Allergy, The No.1 People’s Hospital of Shizuishan, Shizuishan, 753000, Ningxia Hui Autonomous Region, People’s Republic of China; 6Department of Respiratory and Critical Care Medicine, Shenmu Hospital, Shenmu, 719300, Shanxi, People’s Republic of ChinaCorrespondence: Kai GuanDepartment of Allergy, Peking Union Medical College Hospital, #1 Shuaifuyuan, Wangfujing, Beijing, 100730, People’s Republic of ChinaTel +86 10 69151605Fax +86 10 69156346Email dr_guankai@126.comPurpose: Grass pollen is an important cause of IgE-mediated allergy in countries worldwide, especially within Europe. However, there has been no research on grass pollen allergy in northern China. We aimed to determine the status of grass pollen allergy and the sensitization patterns to Phleum pratense (P. pratense) in northern China.Patients and Methods: Pollen data were collected for three geographic areas (Beijing, Shenmu, Shizuishan) in northern China. The study enrolled 101 patients (62 men; age range, 1– 64 years; median age, 10 years) who had allergic rhinoconjunctivitis and/or asthma during the grass pollen season and positive skin prick test results positive to P. pratense. Serum-specific IgE (sIgE) against Phl p 1, Phl p 2, Phl p 5, Phl p 6, Phl p 7, Phl p 12 was measured by ImmunoCAP.Results: The pollen season of P. pratense was from June to September in Beijing, May to September in Shenmu and July to August in Shizuishan. P. pratense pollen accounted for 2– 3% of the annual pollen index of total pollen counts. Among 101 patients with positive skin prick test results to P. pratense, 72% had detectable sIgE to P. pratense. Phl p 12 was the most frequently recognized component (45%), followed by Phl p 1 (22%), Phl p 5 (14%), Phl p 6 (8%) and Phl p 7 (3%). No patients had sIgE to Phl p 2. Ten sensitization patterns to the six components were observed. High rate of sIgE to Phl p 12 was positively correlated with co-sensitization to weed or tree pollen.Conclusion: Considering the pollen concentration, P. pratense was a minor pollen allergen in northern China and its pollen season overlapped with that of weed pollen. IgE sensitization to P. pratense was likely to be induced by cross-reactivity between grass pollen allergy and weed/tree pollen allergy.Keywords: allergic rhinitis, allergen components, grass pollen allergy, Phleum pratense, Phl p 12